A CASE STUDY ON THE WORKING CONDITIONS OF WOMEN WORKERS - KUMARI RANI (International Journal of Multidisciplinary Research and Studies, 2020)
The situation of women and the policies that aim to improve their employment and standard of living need to be viewed in the overarching context of the deteriorating conditions of rural workers, in particular the conditions of landless and near-landless rural households. This is because the conditions of these workers and households are directly related to the conditions of women. Emerging monetarist state policies are leading to the breakdown entailment of social services, the food and agriculture crisis, especially in Africa, and the increased concentration of the poor in the informal sector, which is characterized by incomes that are erratic and unpredictable. All of these factors are having a dramatic impact on the situation in rural areas of developing countries. Low salaries, high unemployment, and deplorable living circumstances are all too often occurrences in the lives of people of both sexes.